EVALUASI PENGELOLAAN SAMPAH DI KOTA DUMAI TAHUN 2018 - Lestari, Dinda Dwiyuni; Febrina, Rury (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
The Department of Environment of the City of Dumai is a government agency that has the authority to hold government affairs in the environmental field, one of which is in the field of waste management,Waste management is a systematic, comprehensive and sustainable activity which includes the reduction and handling of waste. The increasing population growth in Dumai City causes the amount of waste generated every day to increase due to changes in consumption patterns and people's lifestyles, so that waste heaps increase so that special handling needs to be carried out by the Department of Environment.The purpose of this study is to explain the evaluation of waste management in Dumai City in 2018 and the inhibiting factors that influence waste management. The research methodology uses a qualitative approach to the type of descriptive research. This method aims to get a true picture of the evaluation of waste management in Dumai City.Â The results of this study are that waste management in Dumai City in 2018 has not been optimal, this is due to the many obstacles, starting from the strategies used, the way of operation, the way of learning, the implementation of supervision and the implementation of evaluations. The suboptimal strategy can be seen from the lack of budget used to purchase waste management facilities and infrastructure. in the aspect of how waste management operations are currently being carried out have not yet reached the stage of handling and processing of waste so that the resulting waste generation cannot be reduced. In the aspect of selecting ways of learning, it cannot be applied yet because there are no facilities or technology for the process of making compost. In the implementation of supervision, the lack of field supervisors. The main problem in terms of waste management in Dumai City is the lack of budget which results in the lack of facilities and infrastructure in waste management. The factors which hamper this waste management are the limited budget, facilities and infrastructure, and human resources, the absence of local regulations, and the lack of community participation not to litter. Keywords: Evaluation, Government Management, Waste ManagementÂ